2020
DOI: 10.1523/jneurosci.0057-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Poststroke Impairment and Recovery Are Predicted by Task-Specific Regionalization of Injury

Abstract: Lesion size and location affect the magnitude of impairment and recovery following stroke, but the precise relationship between these variables and functional outcome is unknown. Herein, we systematically varied the size of strokes in motor cortex and surrounding regions to assess effects on impairment and recovery of function. Female Sprague Dawley rats (N = 64) were evaluated for skilled reaching, spontaneous limb use, and limb placement over a 7 week period after stroke. Exploration and reaching were also t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 65 publications
(78 reference statements)
3
24
0
Order By: Relevance
“…31 The reasons for this difference between rats and humans is not clear but may be related to the following: (1) inherent differences between rat and human neuroanatomy; (2) rat rehabilitation is better suited to capitalize on SBR with enriched environments, increased time on task, and rehabilitation specifically suited to the outcome measure; and/or (3) a pairing of lesion location and rehabilitation that is better suited to influence recovery in rodents compared with humans. 33 Here, we report recovery of function independent of poststroke training in mice that receive Cerebrolysin (see Figure 1A), similar to the spontaneous recovery seen in stroke patients. Such recovery cannot be because mice receiving Cerebrolysin injections had reduced poststroke deficits immediately after the stroke because our data show that mice tested immediately after stroke (Figures 1A and 1C) had reduced prehension success, similar to prior reports.…”
Section: Spontaneous Recovery In the Poststroke Time-sensitive Periodsupporting
confidence: 76%
See 1 more Smart Citation
“…31 The reasons for this difference between rats and humans is not clear but may be related to the following: (1) inherent differences between rat and human neuroanatomy; (2) rat rehabilitation is better suited to capitalize on SBR with enriched environments, increased time on task, and rehabilitation specifically suited to the outcome measure; and/or (3) a pairing of lesion location and rehabilitation that is better suited to influence recovery in rodents compared with humans. 33 Here, we report recovery of function independent of poststroke training in mice that receive Cerebrolysin (see Figure 1A), similar to the spontaneous recovery seen in stroke patients. Such recovery cannot be because mice receiving Cerebrolysin injections had reduced poststroke deficits immediately after the stroke because our data show that mice tested immediately after stroke (Figures 1A and 1C) had reduced prehension success, similar to prior reports.…”
Section: Spontaneous Recovery In the Poststroke Time-sensitive Periodsupporting
confidence: 76%
“…31 The reasons for this difference between rats and humans is not clear but may be related to the following: (1) inherent differences between rat and human neuroanatomy; (2) rat rehabilitation is better suited to capitalize on SBR with enriched environments, increased time on task, and rehabilitation specifically suited to the outcome measure; and/or (3) a pairing of lesion location and rehabilitation that is better suited to influence recovery in rodents compared with humans. 33…”
Section: Discussionmentioning
confidence: 99%
“…41 This was accompanied by the recovery of performance on a skilled reaching task, although interestingly, in contrast to the current study, deficits on both the cylinder and grid-walking task remained evident, suggesting that different types of sensorimotor function may recover at different rates depending on stroke size and location. 42 Promisingly, emerging studies Ab expression switches from a scattered distribution in the parenchyma of the brain up to 28 days post-stroke to a localisation around the vessels at 84 days post-stroke in the peri-infarct region and in the CA1 sub-region of the hippocampus. At day 84, Ab was observed to accumulate around the cerebral vessels in the peri-infarct region, and a lesser degree in the CA1 subregion of the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…41 This was accompanied by the recovery of performance on a skilled reaching task, although interestingly, in contrast to the current study, deficits on both the cylinder and grid-walking task remained evident, suggesting that different types of sensorimotor function may recover at different rates depending on stroke size and location. 42 Promisingly, emerging studies have shown that the modulation of GABAergic signalling using pharmacological approaches 37,43 or optogenetic stimulation 44 after stroke can promote motor recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Predictions of poststroke outcomes in patients are useful to develop more effective therapies in individuals such as the rehabilitation with appropriate intensity and dose. Prognostic factors in lesion size and location were systematically examined in a rat model ( Jeffers et al, 2020 ). Our present study demonstrates potential neural substrates that could determine the recovery process among different CST and lesion types.…”
Section: Discussionmentioning
confidence: 99%